Evaluation of Genetic Diversity Using Parameters Based on Probability of Gene Origin in the Slovak Spotted Bulls - E. Hazuchová; O. Kadlečík; I. Pavlík; R. Kasarda (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this study was to assess the diversity based on probability of gene origin in Slovak Spotted bulls. The pedigree information was available from The Breeding Services of the Slovak Republic, s. e. The pedigree file consisted of 752 individuals. The 62 sires born from 1995 to 2009 and registered in Herd book set up the analyzed reference (RP) population. Total number of founders in the RP was 308, effective number of founders was 115 and the effective number of ancestors was 37. The number of ancestors explaining 50 % of the diversity was 15 and founder’s genome equivalent was 20.46. The sire GS Malf and Horwein were with 16 offspring’s the most frequently used bulls in the artificial insemination. We found that the genetic conservation index for RP was 16.34 %. Results will be used in genetic management of breeding work in Slovak Spotted and monitoring of parameters characterizing genetic diversity and their development, as well.